(untitled) (Journal of the Sociology and Theory of Religion, 2018)
The trilogy La Modernidad without prejudice is reviewed here. Religion in American public life, by Dr. Antonio Sánchez-Bayón, specialist in Political-Legal History and Philosophy, as well as Law and Comparative Politics. Although separated in three volumes, these three monographs (one of cultural foundations, another of normative politico-legal and the last on discourses) actually correspond to a single work, complete and round (on the influence of religion in public life American and its idiosyncratic development as a people).